Improving students' martial arts skills and fitness through an innovative e-module - Nova Risma; Syahrial Bakhtiar; Umar; Fiky Zarya (Sport TK)
The aim of this study was to develop the Physical Education, Sports, and Health module by incorporating pencak silat material along with physical fitness activities to enhance the physical fitness of seventh-grade students. The Borg and Gall model, which comprises potential and issues, data gathering, product design, design validation, design revision, product testing, and product revision, was the research methodology that was employed. Lecturers, instructors, and students composed the research population. Validation sheets were used for validators and questionnaires were used for students during the data gathering phase. Professionals in the martial arts used a grid to evaluate students' skills. In the meanwhile, to evaluate students' physical fitness, the Harvard Step Up Test was used. The following results were obtained: 1) The last module (E) is highly practical to utilize as martial arts lesson material for class VII students, along with physical fitness training exercises. 2) Utilizing e-modules to learn can enhance students' proficiency in fundamental martial arts techniques. 3) Students' physical fitness improves when physical fitness training exercises are integrated with martial arts skills. In conclusion, the pencak silat learning e-module, which is backed by physical fitness training, is deemed extremely viable to be utilized as teaching material and enhance students' physical fitness.